2014
DOI: 10.1099/vir.0.068411-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection and injury of human astrocytes by tick-borne encephalitis virus

Abstract: Tick-borne encephalitis (TBE), a disease caused by tick-borne encephalitis virus (TBEV), represents the most important flaviviral neural infection in Europe and north-eastern Asia. In the central nervous system (CNS), neurons are the primary target for TBEV infection; however, infection of non-neuronal CNS cells, such as astrocytes, is not well understood. In this study, we investigated the interaction between TBEV and primary human astrocytes. We report for the first time, to the best of our knowledge, that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
100
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 65 publications
6
100
2
Order By: Relevance
“…3B,4A–D). Similar structures were previously demonstrated in the RER of other vertebrate or arthropod cells infected with TBEV19, Langat virus20, and mosquito-borne flaviviruses162122. In a previous study, we observed virus-induced vesicles and viral particles directly attached to tubule-like structures in the RER of TBEV-infected human primary astrocytes19.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…3B,4A–D). Similar structures were previously demonstrated in the RER of other vertebrate or arthropod cells infected with TBEV19, Langat virus20, and mosquito-borne flaviviruses162122. In a previous study, we observed virus-induced vesicles and viral particles directly attached to tubule-like structures in the RER of TBEV-infected human primary astrocytes19.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies reported tubule-like structures that ranged from 50 to 100 nm in diameter and from 100 nm to 3.5 μm in length20212223. In TBEV-infected human astrocytes, we previously observed tubule-like structures of 17.9 nm (±0.2 nm) in diameter19. The function of tubule-like structures is not clear.…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with this, it has been shown that increased expression of TNF-α after infection with WNV and JEV is correlated with neuronal death [154,195], and that neutralizing antibodies specific for IL-1β and TNF-α protected neurons from WNV-induced cell death [195]. The release of inflammatory cytokines by neurons can trigger gliosis (i.e., microglial and astrocyte activation), which is one of the major hallmarks of arboviral neuropathogenesis [154,186,198].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 51%
“…Activated astrocytes and microglia play an important role in inflammatory responses during natural infection with encephalitic flaviviruses, namely JEV [200], WNV [201], and TBEV [198], as well as encephalitic alphaviruses [186]. Upon activation, astrocytes and microglia release several chemokines and cytokines such as TNF-α, IL-6, C-X-C motif chemokine ligand (CXCL)10, chemokine (C-C motif) ligand 2, monocyte chemoattractant protein-1, RANTES, IFN-γ-induced protein 10, and matrix metalloproteinases [154,195,[202][203][204].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…In the present study, human enteroviruses (hEV) and tick-borne encephalitis virus (TBEV) were included, as they are both neurotropic, although not oncogenic, in order to define their possible association with brain tumours. TBEV can cause the relatively common flaviviral infection in Europe, including Slovenia (32), and Palus et al (33) reported on the link between TBEV infection and astrocyte injury. Taken together, the presence of this plethora of viruses in glioma, their carcinogenic activities, and their roles in glioma progression all remain unclear.…”
mentioning
confidence: 99%